Improving English Vocabulary Mastery using Word Square Method - Tiara, Ana; Sudarmaji, Imam; Nuraini, Hery; Forsia, Lastry; Nirmala, Nirna (Universitas Pahlawan Tuanku Tambusai, 2024)
Students who study foreign languages have weaknesses in the vocabulary they learn. The aim of this research is to determine the process of increasing students' vocabulary mastery through the word square game in class II elementary school students in the city of Tangerang for the 2023/2024 school year. The subjects of this research were second grade elementary school students for the 2023/2024 academic year. This class consists of 11 students. This research uses quantitative methods. The results of the analysis in collecting data, researchers use tests. The tests were given in the form of pre-test, post-test 1 and post-test 2. Researchers analyzed the average score of each test to determine the increase in students' vocabulary mastery after carrying out these actions. students' mastery of skills increases optimally. This can be seen from the pre-test score of 80, post-test 1 90, and post-test 2 92.27. After implementing the actions, researchers were able to solve problems in increasing mastery of understanding. Students are able to understand the meaning of words based on the context. By using the word square game in vocabulary learning, students can easily understand and memorize new vocabulary. In the vocabulary learning process, when the teacher uses the word square game, students look very enthusiastic and enjoy the learning process.